2014
DOI: 10.1590/s0102-6720201400s100014
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y gastric bypass: limb length and weight loss

Abstract: BackgroundRoux-en-Y gastric bypass is a surgical technique widely used in the treatment of obesity. It is unclear, however, if the length of the biliopancreatic and alimentary limb interferes with the magnitude of weight loss.AimTo evaluate if the length of these limbs is related to the percentage of weight loss one year after surgery.MethodOne hundred and twenty obese people underwent surgery between 2009 and 2011. Patients were inserted into four groups: A) biliopancreatic limb with 50 cm length and alimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
0
9
0
1
Order By: Relevance
“…Despite the invention of new bariatric surgical procedures, RYGB has been considered as a gold standard procedure which is malabsorptive and restrictive [10,15]. The impact of BPL and AL lengths on RYGB outcomes is still controversial regarding appropriate limb lengths [6,8,10,11,[15][16][17][18], de-spite the established relationship between patients' height and total small bowel length [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the invention of new bariatric surgical procedures, RYGB has been considered as a gold standard procedure which is malabsorptive and restrictive [10,15]. The impact of BPL and AL lengths on RYGB outcomes is still controversial regarding appropriate limb lengths [6,8,10,11,[15][16][17][18], de-spite the established relationship between patients' height and total small bowel length [15].…”
Section: Discussionmentioning
confidence: 99%
“…The role of alimentary and biliopancreatic limb length in outcomes of Roux-en-Y gastric bypass limb (AL) length on the outcomes of RYGB patients [6][7][8][9][10][11], and there is not yet any consensus on the appropriate length of the BPL, AL, and common limb. Previous studies have reported contradictory results in efficacy of these limb lengths to achieve the best results in weight loss outcomes and the prevention of nutritional complications.…”
Section: Different Findings Have Been Obtained About the Effect Of Bimentioning
confidence: 99%
“…In the current form of the RYGB (Fig. 1A), a gastric sleeve pouch is created of approximately 20-30 mL volume using a 36-42 French bougie with an alimentary limb of approximately 120-150 cm in length and a biliary limb of approximately 50-100 cm in length, depending on the individual technique (86). Both gastrojejunal and jejuno-jenunal anastomosis can be created using stapler devices and sutures.…”
Section: Roux-en-y Gastric Bypassmentioning
confidence: 99%
“…Many studiesconcur that the CL length and AL length do not affect the amount of potential weight loss that a patient can achieve [25][26][27][28] though Tran et al [29] has suggested the use of a distal bypass is an effective revision for a failed loss of weight on a standard bypass. There is certainly a range of results on whether proximal or distal bypasses have more pronounced effects on the metabolic and endocrine systems as reported by Risstad et al [9] and Ramos et al [30] Distal bypasses may also be related to increased rates of complication.…”
Section: Authors' Contributionsmentioning
confidence: 99%